A inclusão da pessoa com deficiência e com transtornos globais do desenvolvimento nos cursos de direito de Vitória (ES): limites e possibilidades de ingresso e permanência - Fernandes, Luana Siquara (2018)
The present research analyses the limits and possibilities of admission and permanence of a person with disabilities and with Developmental Disorders (Pervasive Developmental Disorders – PDD), in the Law School of Vitoria (ES). Adopted as a scientific methodology the intuitive method followed by techniques of bibliographic research, as well as the realization of the research in the field, through the development of semi structured interviews with the participating subjects, between the coordinators of the Law School of Vitoria and the disabled and or developmentally delayed students enrolled in these. The first part of the work is intended to present the paradigmatic moments that influenced the development of what is today referred to as special education. For that reason, some of the historical periods of social recognition of the disabled, are revisited; the legal contours of this education in Brazil are outlined; the concepts of equality and difference are analyzed, as well as their relationship to each other. The scope of the second part of this work is to analyze special education from the perspective of the day to day reality of higher education, specifically in the Law courses considered as core courses of the same. With this objective the contributions of the Boaventura de Sousa Santos about the Sociology of Absence, will be used as a conduit to reach the redetermination of the levels of higher education. The third and last part of the work is intended to present the results obtained in the development of the research in the field. This way the reasoning of the participants and its analysis is available in the form of a Text, table and designs. The data obtained, when analyzed for the theoretical reference utilizing the course of the research, make it possible to identify the limits verified and the possibilities noticed by the interviewed, in reference to an effective inclusion of the person with disabilities and with developmental disorders within the Law courses.